Intergroup Processes: A Micro Macro PerspectiveIntergroup Processes: A Micro Macro Perspective, by Blalock Hubert M. Jr Wilken Paul H.. New York: Free Press, 1979, 645 pp., $24.95 cloth. - Fombrun, Charles J. (Academy of Management Review, 1982)
The article reviews the book ?Intergroup Processes: A Micro Macro Perspective,? by Hubert M. Blalock, Jr. and Paul H. Wilken.